Effect of the end-wall vortex generator jets on the performance of a high subsonic compressor cascade. (May 2019) - Chen, Cong; Liu, Huaping; Chen, Fu
This paper presents a numerical and experimental result of the end-wall vortex generator jets for controlling corner separation and enhancing the aerodynamic performance in a high subsonic (Ma = 0.7) compressor cascade. The experiments were carried out on a compressor cascade at design point ( i = 0°) and off-design points ( i = −2°, 2°, and 4°). At design point, the total pressure loss coefficient could be reduced up to 12.1%.With the increase in the incidence, the control effect is enhanced first and then reduced. The maximum total pressure loss reduction is up to 14.6% when the incidence is 2°. The numerical study is further conducted to analyze the flow pattern and the vortex structure. The jet vortex is formed downstream of the jet hole using the vortex generator jets, the cross flow on the end wall is also suppressed.